THE IMPLEMENTATION OF SARI SWARA METHOD IN CHILDREN'S EDUCATION AT TAMANSISWA EDUCATION INSTITUTION OF YOGYAKARTA IN 1922-1942 - Reza Oky Iswiranto (Satmata: Journal of Historical Education Studies, 2024)
This research aims to (1) know the history of the establishment of Tamansiswa Education Institution of Yogyakarta; (2) examine the process of creating the Sari Swara method by Ki Hadjar Dewantara; and (3) study the implementation of Sari Swara method in children’s education at Tamansiswa Education Institution of Yogyakarta in 1922-1942. This research method is historical research. According to Kuntowijoyo, steps in historical research include topic selection, source collection, verification, interpretation, and historiography. The results of this study are: (1) Tamansiswa Education Institution of Yogyakarta was established on July 3, 1922, initiated by Ki Hadjar Dewantara after he joined the Paguyuban Selasa Kliwon. Tamansiswa Education Institution of Yogyakarta prioritizes the educational process to foster character value in children; (2) Ki Hadjar Dewantara created the Sari Swara method by developing the concept of Sastra Gendhing from Sultan Agung and combining education thoughts from world figures. The Sari Swara method uses education means that it comes from the community, is in accordance with the nation’s lifeline, and contains character values. (3) The implementation of Sari Swara method in Tamansiswa Education Institution of Yogyakarta through the implementation of Sistem Among and using the means, such as tembang (songs) and dolanan (children’s games) that have developed in the community since long ago.